2003
DOI: 10.1089/153056203763317666
|View full text |Cite
|
Sign up to set email alerts
|

Rural Interdisciplinary Mental Health Team Building via Satellite: A Demonstration Project

Abstract: This paper reports on the results of a demonstration project that examined the role of telehealth/telemedicine (hereafter referred to as telehealth) in providing interdisciplinary mental health training and support to health professionals in a rural region of Atlantic Canada. Special emphasis was placed on addressing the question of how training might affect interdisciplinary collaboration among the rural health professionals. Five urban mental health professionals from three disciplines provided training and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 11 publications
4
20
0
1
Order By: Relevance
“…When communities have been able to secure these resources, they have found this technology to be appropriate for working with adolescents (Ermer, 1999). This technology has also been used to provide interdisciplinary training in rural areas via videosatellite conferencing (Cornish et al, 2003).…”
Section: Strategies To Address Issues At the Ontogenetic Levelmentioning
confidence: 99%
“…When communities have been able to secure these resources, they have found this technology to be appropriate for working with adolescents (Ermer, 1999). This technology has also been used to provide interdisciplinary training in rural areas via videosatellite conferencing (Cornish et al, 2003).…”
Section: Strategies To Address Issues At the Ontogenetic Levelmentioning
confidence: 99%
“…Developing such relationships from a distance is possible but extremely time consuming and costly (Cornish et al, 2003;McGrath et al, 2009). These factors may place local psychologists in an excellent position to effectively distribute accurate information about self-directed and telepsychology services that may, in turn, enhance willingness to access such services and reduce barriers related to anonymity, independence, and self-reliance.…”
Section: Recruiting and Retaining Randn Psychologistsmentioning
confidence: 99%
“…However, acceptance research has been conducted in telehealth -the overall ICT health care delivery system, which includes televisitation. The literature review on telehealth acceptance showed that the implicit -connotative part of attitudes had not been studied (Aarnio et al, 2000;Bowater, 2001;Cheung et al, 1998;Cornish et al, 2003;Davis et al, 2001;H. Lamminen, Tuomi, J. Lamminen, & Uusitalo, 2000;Ho & Jarvis-Selinger, 2005;Jong & Kraishi, 2004;Kumar et al, 2006;Lavoie, 2010;Linassi & Li Pi, 2005;Miller & Levesque, 2002;Ohinmaa, Vuolio, Haukipuro, & Winblad, 2002;Persaud et al, 2005;Saqui et al, 2007).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The attitudes toward telehealth have been studied in a variety of ways. A review of telehealth literature shows that there have been several studies conducted for measuring satisfaction towards telehealth (Aarnio et al, 2000;Cheung et al, 1998;Cornish et al, 2003;Davis et al, 2001;Ho & Jarvis-Selinger, 2005;Linassi & Li Pi, 2005;Miller & Levesque, 2002;Saqui et al, 2007).…”
Section: Satisfaction With Telehealthmentioning
confidence: 99%
See 1 more Smart Citation